2015
DOI: 10.1097/opx.0000000000000574
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma Patient Expression of Medication Problems and Nonadherence

Abstract: Purpose The purpose of this study was to examine if patient demographic factors influenced self-reporting of medication side effects, difficulty with drop instillation and nonadherence to glaucoma therapy. Methods English-speaking adult glaucoma patients (n=279) from six ophthalmology clinics were enrolled. Patients’ medical visits were videotaped and patients were interviewed immediately afterwards by research assistants. The videotapes were transcribed verbatim and coded to identify patients who expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Laser trabeculoplasty is often as effective as a single medication for lowering IOP and has been reported to have few adverse effects [28]. Topically applied medications can be effective at lowering IOP, but their effectiveness is based on a patient's ability to maintain their daily treatment plan [29,30]. Adherence to glaucoma medication requires the patient to consistently perform specific actions, including appropriately administering eyedrops (i.e., ability to instill a drop within the eye) and continuing to instill drops as prescribed.…”
Section: Overview Of Adherence and Persistence In Glaucomamentioning
confidence: 99%
See 1 more Smart Citation
“…Laser trabeculoplasty is often as effective as a single medication for lowering IOP and has been reported to have few adverse effects [28]. Topically applied medications can be effective at lowering IOP, but their effectiveness is based on a patient's ability to maintain their daily treatment plan [29,30]. Adherence to glaucoma medication requires the patient to consistently perform specific actions, including appropriately administering eyedrops (i.e., ability to instill a drop within the eye) and continuing to instill drops as prescribed.…”
Section: Overview Of Adherence and Persistence In Glaucomamentioning
confidence: 99%
“…A patient may purport to be adherent but is actually using a medication incorrectly or not taking any medication due to difficulty self-administering drops. Numerous studies in the United States and other countries have documented that poor technique is a considerable concern in nonadherence [29,[65][66][67][68][69].…”
Section: Issues With Self-administrationmentioning
confidence: 99%
“…A study by Slota et al identified that patients often felt more comfortable expressing treatment concerns to research assistants (at 41% of the cohort), rather than their treating ophthalmologist (at 10%). [20] A POEM can be a useful tool in providing transparency and in helping a team of clinicians to adapt their practice by highlighting any deficiencies that can be addressed in the consultation. Question 3 demonstrated that patients were very accepting of the treatment and possible side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Side effects, even those deemed too minor to report to clinicians, are known to decrease medication adherence, as patients are more likely to self-titrate by reducing or missing doses in order to reduce side effect symptoms. [33][34][35][36] The effects of side effects on decreased medication adherence have been observed in patients with chronic conditions, such as hypertension 31,32 , diabetes 30 , and mental health disorders 29 . Furthermore, although nearly all participants began treatment with 300 mg/day, the lower the predicted function of CYP2C9, the more likely participants were to have a lower dose after one year.…”
Section: Discussionmentioning
confidence: 99%